Effectiveness of the project writing training developed for pre-service primary teachers - Güler Göçen Kabaran; Sedat Altıntaş (Journal of Education and Learning (EduLearn), 2022)
The study investigated the effectiveness of the project writing training developed and implemented for pre-service primary teachers. A case study was adopted in the research. The participants of the study were 17 students of the department of primary school teaching at nine different universities in Turkey. In this context, an online project preparation training was given to participant pre-service primary teachers. The prepared training was presented to pre-service teachers as theoretical and practical. At the end of this process, pre-service teachers were provided to prepare project proposals under the guidance of academic consultancy. A semi-structured interview form developed by the researchers was used to collect the research data. The obtained data were subjected to descriptive and content analysis. Within the scope of the research, it was determined that the participant pre-service teachers had positive opinions about the planning of the developed education and its contribution to them. It was concluded that some of the participants had negative opinions about the duration, timing and onlineness of the training.